Association of diuretics with falls and wrist fractures: a Mendelian randomization study - Liu, Fei; Dai, Jun-ze; Deng, Xiao-xi; Cao, Ren-shuang; Cheng, Yong-zhong; Wang, Chao-lu (Frontiers in Public Health, 2024)
BackgroundThe association between diuretics and falls in older adult has been reported in previous studies, but discrepancy remains between the different types of diuretics. The association of diuretics with the risk of wrist fractures due to diuretics is also unclear. Therefore, in this study, we determined the association of diuretics with falls and wrist fractures by Mendelian randomization.MethodsWe used a two-sample Mendelian randomization (MR) approach to evaluate the effects of the loop diuretics-sparing diuretics hiazide diuretics (LDs) on the risk of falls and wrist fracture using the three diuretic-associated genetically-predicted single nucleotide polymorphisms (SNPs) as genetic tools. The inverse variance weighting (IVW) method was used as the main evaluation method, with odds ratio (OR) as the evaluation criterion. Additionally, weighted median (WME), MR-Egger, weighted mode (WM) and simple mode (SM) methods were used together for the MR analysis, and sensitivity analyses were performed to assess the robustness of the main results.ResultA total of 35 SNPs were included in this study as instrumental variables to replace LDs, PSDs, and TDs, which were 24, 7, and 4. Genetic substitutions for diuretics associated with increased risk of falls were LDs (OR = 1.012043, 95%CI: 1.001607–1.022588, p = 0.022337), PSDs (OR = 1.023794, 95%CI: 1.005605–1.042312, p = 0.010138). Genetically proxied TDs showed no association with falls, but the use of TDs showed a negative correlation with the incidence of wrist fracture (OR = 0.833, 95%CI: 0.767–0.905, p < 0.001). The Cochran Q-test showed no heterogeneity and MR-PRESSO method excluded data pleiotropy.ConclusionOur findings suggest that the use of loop diuretics (LDs) or potassium-sparing diuretics (PSDs) increases the incidence of falls, but there is no causal relationship between thiazide diuretics (TDs) and falls, and TDs may actually reduce the risk of wrist fractures. Clinical use of diuretics necessitates vigilance and appropriate preventive measures to minimize fall-related events.